Development of Logic-Based Question Classification Methods to Measure the Ability to Ask Questions Essential for Setting Research Questions - Qiu, Li; Ikeda, Fumihito; Yamashita, Naoko (Integrated Science Education Journal, 2024)
Purpose of the study: Many learners experience difficulties in generating questions that lead to research questions. This study aimed to present perspectives on questions that inquire into the logic within each type of logical reasoning, propose a new question classification method based on these perspectives, verify its objectivity, and examine participants' logicality. Methodology: This study deductively developed perspectives and classification methods for questions based on the logical reasoning theory. To verify the question-classification method and examine participants' logicality, 1,164 Self-described questions from 24 graduate-level students were collected. These questions were classified by two raters using qualitative research software, followed by a statistical analysis. Descriptive and inferential statistics were used for the analysis. Main Findings: Based on the analysis of the question data, the degree of agreement on question classification between the two raters was high. Notably, there was exceptional concordance in categorizing questions asking about deductive reasoning, hypothetical reasoning, and specific questions. Additionally, the analysis of question characteristics revealed a predominant presence of questions asking about inductive reasoning and ambiguous questions. In contrast, there were fewer questions asking about deductive reasoning, hypothetical reasoning, and specific questions. Novelty/Originality of this study: This research adds a logical perspective to traditional question frameworks and develops objective question classification methods. It provides a framework to support the formation of questions that lead to research questions and a method to objectively assess the quality of learning question formation techniques, with significant implications for educational practices. This study is limited by few raters, few specific questions.